Repeated implementation with overlapping generations of agents - Helmuts Azacis (Cardiff University, Cardiff Business School, 2017)
We study repeated implementation in a model with overlapping generations of agents.It is assumed that the preferences of agents do not change during their lifetime.A social choice function selects an alternative in each period as a function of the preferences of agents who are alive in that period.We show that any social choice function satisfying mild necessary conditions is repeatedly implementable in subgame perfect equilibrium if there are at least three agents and they live sufficiently long.
Keywords: C72; C73; D71; D82; 330; Repeated Implementation; Subgame Perfect Implementation; Overlapping Generations; Necessary and Sufficient Conditions